The Influence Financial Advisor Recommendations on the Investment Decisions of Student Investor in Medan With Intention as a Predicator and Financial Literacy as Moderator - Alistraja Dison Silalahi; Sri Wardany; Cita Ayni Putri Silalahi; Shita Tiara (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to find and analyze the effect of financial advisor recommendations on investment decisions of students in Medan with the intention as a mediator and financial literacy as a moderator. This research is a quantitative research with an explanatory research model, with primary data. Data collection techniques using a questionnaire. The data analysis technique is statistical analysis based on partial least squares. The results of the study found that financial advisor recommendations have an effect on investor intentions. Investor intention influences investment decision. Financial advisor recommendations influence investment decisions. Financial literacy has no effect on investor intentions. Investor intent significantly mediates the relationship between financial advisory recommendations and investment decisions. Financial literacy does not moderate the effect of financial advisor recommendations on investment intentions.